Reproduction in the digital age: the adaptation of Morlum from Edutainment to Advertainment - วรรณอุดม, ประยุทธ (Journal of Management Science Chiangrai Rajabhat University, 2018)
In the concept "The Work of Art in the Age of Mechanical Reproduction" of Walter Benjamin argued that the new technology of mass media is the tool to carry out the work of art reproduced for everyone to share that admirable art. Thus, we generalize the concept of Benjamin with the phenomenon of Morlum, popular folk culture of Northeastern in Thailand which can be seen that the "new technology reproduce a unique work of art”. Hardwares and softwares make the chances for everyone to see and hear Morlum in the world. We see a general audiences (not the capitalist of mass media) can produce the work of Morlum to broadcast via social media like Youtube or by other websites .The interesting phenomenon is the online world in an “Age of mechanical reproduction art” makes Morlum adapt and change themselves from edutainment to be advertainment .